Do family ties with those left behind intensify or weaken migrants' assimilation? - Oded Stark; Agnieszka Dorn (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
Strong ties with the home country and with the host country can coexist. An altruistic migrant who sends remittances to his family back home assimilates more the more altruistic he is, and also more than a non-remitting migrant.
urn:nbn:de:bsz:21-opus-64313
Keywords: D01; D13; D64; F22; F24; 330; Assimilation of migrants; Acculturation identity; Links with the home country; Altruism; Remittances